Variants of psychopathic personality in Korean and UK incarcerated offenders: Using latent profile analysis and discriminant analysis. Issue 2 (16th November 2021) - Reale, Kylie S.; Lee, Joohyung; Sea, Jonghan
Abstract: Since the popularization of the Psychopathy Checklist‐Revised (PCL‐R), research on the construct of psychopathy has drastically increased. However, there has been little research examining the extent to which psychopathy varies across different cultures. This study is the first to use latent profile analysis to examine cultural variations in psychopathic traits between large samples of male inmates in Korean ( n = 1102) and UK ( n = 1316) prisons. Supplementary discriminate analysis was also used to validate the classification profiles and determine which items of the PCL‐R were most important in defining the differences or similarities between each of the classes in the two large samples. Based on the analysis, two variants of primary psychopathy could be distinguished in the Korean sample but not in the UK sample. Conversely, only secondary psychopathy was identified in the UK sample. This result was also confirmed by supplementary analysis, which verified classification accuracy and also provided structure matrixes listing the correlations between each PCL‐R item and the two discriminant functions. Our results point to the possibility of cultural differences in the structure of psychopathy and provide practical implications for clinical assessment and diagnosis.